Kontribusi Kondisi Fisik Terhadap Kemampuan Servis Bawah Dalam Permainan Bolavoli - La Kamadi (Journal Coaching Education Sports, 2020)
This type of descriptive research which is contributive which aims to determine the strength of the arm muscles, hand eye coordination and balance of the ability to serve under volleyball in students of SMP Negeri 2 Balocci, Pangkep Regency. Student population of SMP Negeri 2 Balocci, Pangkep Regency, as many as 30 samples. The data were collected using the arm muscle strength test instrument (Push Up per 30 seconds), hand eye coordination test, dynamic balance test and volleyball under-serve ability test. The results of the study: 1) There is a significant and linear contribution of arm muscle strength to the ability to serve under volleyball of = 44.70% with a regression coefficient of Î± = 0.344 (P = 0.000). 2) There is a significant and linear hand-eye coordination contribution to the ability to serve under volleyball by 31.80% with a regression coefficient of Î± = 0.735 (P = 0.000). 3) There is a significant and linear balance contribution to the ability to serve under volleyball of = 55.20% with a regression coefficient of Î± = 0.140 (P = 0.000). 4) There is a significant and linear contribution of the combination of arm muscle strength, hand eye coordination, and balance to the ability to serve under volleyball by 98.90% with F = 795,684 (P = 0,000) and the regression equation Y = 17.304 + 0.344 X1 + 0.727 X2 - 0.133 X3.